BASIC METHODOLOGICAL PRINCIPLES OF TEACHING GYMNASTIC CLASSES TO CHILDREN - Kamola Khakimdjanova; Dilfuza Achilova (Proximus Journal Publishing, 2024)
In this article, one of the main stages of teaching gymnastics, which is the queen of sports, is about teaching methods, training procedures and their proper organization during the school period, which is one of the main periods. data are cited.
Keywords: Gymnastics; training; sports field; equipment